Impacts of COVID-19 on Food Security in Cox's Bazar : Food Consumption, Coping and Assistance - World Bank (World Bank, Washington, DC, 2021)
This brief presents findings on consumption, coping and basic needs from the Cox’s Bazar Panel Baseline Survey (CBPS) conducted between March – August, 2019 in combination with findings from the first rapid follow-up on a sub-sample of the baseline households conducted between April-May 2020. Baseline data was collected from 5,020 households across camp and host settlements (camp settlements are defined as areas within the camp boundaries set by the government, UNHCR and IOM jointly, host settlements are defined as all areas outside of the camp boundaries within the district). A 3-hour walking distance was used as a cut-off to segregate host areas as being high and low exposure to the influx. In addition to baseline pre-COVID findings, the analysis presents updated topline statistics on the current situation of access to basic needs drawn from a rapid phone follow-up of 3,150 households across camps, high and low exposure host communities.